2021
DOI: 10.4269/ajtmh.20-0659
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Early In-Hospital Antivenom Administration to Patients with Protobothrops mucrosquamatus Envenomation

Abstract: Protobothrops mucrosquamatus is one of the common venomous snakes in Southeast Asia. This retrospective cohort study conducted in six medical institutions in Taiwan aimed to obtain information on the optimal management strategies for P. mucrosquamatus snakebite envenomation. Data were extracted from the Chang Gung Research Database from January 2006 to December 2016. The association between early antivenom administration and patient demographics, pain requiring treatment with analgesic injections, and hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Recent studies have reported that the secondary wound infection rates in patients envenomed by P. mucrosquamatus and T. stejnegeri are approximately 25% and 12%, respectively [ 9 , 33 , 34 ]. When envenomed by B. multicinctus , the infection rates are much lower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported that the secondary wound infection rates in patients envenomed by P. mucrosquamatus and T. stejnegeri are approximately 25% and 12%, respectively [ 9 , 33 , 34 ]. When envenomed by B. multicinctus , the infection rates are much lower.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, there are 1.2–5.5 million snakebites each year, of which 125,000 result in death or disability, especially in Southeast Asia [ 5 , 6 ]. There are six major venomous snakes in Taiwan, specifically Naja atra , Bungarus multicinctus , Protobothrops mucrosquamatus , Trimeresurus stejnegeri , Deinagkistrodon acutus, and Daboia siamensis [ 7 , 8 , 9 ]. About 800–1000 people experience venomous snakebites in Taiwan every year [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 Delayed coagulopathy has been reported sporadically in rattlesnake envenomation. 8 Recent studies 9,10 have shown that the sooner the serum is administered, the better the therapeutic outcome and recovery. Although large amounts of serum were administered in a timely manner, both patients still needed surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Although early antivenom administration would benefit wound recovery and reduce pain in affected patients [7,8], the optimal antivenom administration strategy for D. siamensis envenomation remains unclear. Compared to a recent study [3], most patients with D. siamensis envenomation were administered 4-6 vials of antivenom.…”
Section: Discussionmentioning
confidence: 99%